Towards Effective Academia-Industry Collaborations: The Case of Higher Learning Institutions in Tanzania - Simba Ikuja, Fatuma; V. Haule, Liberato; Machuve, Juliana (Tanzania Journal of Engineering and Technology, 2025)
Industries are the main consumers of products from higher learning institutions (HLIs); graduates for employment and research outputs for socio-economic development. Research outputs from HLIs are commercialized as services or products facilitated by academia- industry collaborations. The collaborations are expected to address mismatch between labour market needs and HLIs’ products, which has resulted in graduates’ employability challenges. Despite their importance, effective academia-industry collaborations remain challenging. This study explores the effectiveness of Academia- Industry collaborations established by HLIs in implementing the Higher Education Economic Transformation (HEET) project (2021- 2026) in Tanzania. One of the project objectives is to build functional linkages between industry and HLIs to align graduates with needs of labour market. The study explored the quantity and types of collaborations established, enablers and barriers, strategies to align graduates with market needs, and sustainability. Using a mixed- method approach, data was collected from eighteen out of nineteen participating institutions through an open-ended questionnaire. By June 2024, HLIs had established 2 to 23 collaborations, with joint research being the most common type of collaboration. Key enablers were institutional support and mutual benefit. Funding constraints and bureaucratic delays were the common barriers. Strategies for aligning HLIs outputs with market needs included enhancing practical skills for both staff and students, curriculum reviews, and institutionalizing the collaboration. Engagement, formal agreements and regular reviews were the strategies for collaboration sustainability. The study results serve as useful feedback to the HLIs, industries, and inputs to policymakers in facilitating effective academia-industry collaborations.